STRES AKADEMIK DAN POLA MAKAN PADA MAHASISWA KEPERAWATAN TINGKAT AKHIR - Sanger, Ailine Yoan; Mamuko, Anjellina (Klabat Journal of Nursing, 2025)
Eating pattern is an important component in maintaining body balance, improving immunity, preventing various diseases, and supporting the academic performance of students in facing various academic pressures. Lack of education causes many people to be unaware of the adverse effects of an imbalanced diet. This study aims to analyze the relationship between academic stress and eating patterns among final-year nursing students at Klabat University. The research method used is a descriptive correlational approach through a cross-sectional design with total sampling technique of 98 respondents. The two instruments—academic stress, measured using the Perceived Academic Stress Scale (PASS), and eating patterns—were adapted from previous questionnaires, which had been validated and tested for reliability with Cronbach's Alpha of 0.83 for academic stress and 0.70 for eating patterns. Data analysis using Pearson’s correlation test revealed a significant and negative correlation between academic stress and eating patterns (r = -0.329; p = 0.001). This means that higher levels of academic stress are associated with poorer eating patterns among students. These findings highlight the importance of stress management strategies and nutrition education as part of promotive-preventive efforts to enhance student well-being. Recommendations for future researchers include exploring other factors that may mediate the relationship between academic stress and eating patterns, such as coping mechanisms, sleep quality, and social support, as well as implementing interventions based on mindfulness, nutrition counseling, and the use of health companion apps to sustainably improve students' eating patterns. Pola makan merupakan komponen penting dalam menjaga keseimbangan dan meningkatkan daya tahan tubuh, mencegah berbagai penyakit kronis serta mendukung performa akademik mahasiswa dalam menghadapi berbagai tekanan akademik. Kurangnya edukasi menyebabkan banyak orang tidak menyadari dampak buruk dari pola makan yang tidak seimbang. Penelitian ini bertujuan untuk menganalisis hubungan antara stres akademik dengan pola makan pada mahasiswa keperawatan tingkat akhir Universitas Klabat. Metode penelitian yang digunakan adalah deskriptif korelasi melalui pendekatan cross sectional dengan teknik Total Sampling pada 98 responden. Kedua instrumen yaitu stress akademik yaitu Perceived Academic Stress Scale (PASS) dan pola makan, diadaptasi dari kuesioner sebelumnya, yang telah diuji validitas dan reliabilitasnya dengan nilai Cronbach’s Alpha sebesar 0,83 untuk stress akademik dan 0,70 unutk pola makan. Hasil analisis data menggunakan uji korelasi Pearson menunjukkan adanya hubungan negatif yang signifikan antara stres akademik dan pola makan (r = -0,329; p = 0,001). Artinya, semakin tinggi tingkat stres akademik, maka semakin buruk pola makan mahasiswa. Temuan ini menunjukkan pentingnya strategi manajemen stres dan edukasi gizi sebagai bagian dari upaya promotif-preventif dalam meningkatkan kesejahteraan mahasiswa. Rekomendasi bagi peneliti selanjutnya adalah untuk mengeksplorasi faktor-faktor lain yang dapat memediasi hubungan antara stres akademik dan pola makan, seperti mekanisme koping, kualitas tidur, dukungan sosial, serta melakukan intervensi berbasis mindfulness, konseling gizi, dan penggunaan aplikasi pendamping kesehatan untuk memperbaiki pola makan mahasiswa secara berkelanjutan.